INOVASI PEMBELAJARAN BAHASA INGGRIS DALAM MENUMBUHKAN BUDAYA ILMIAH MAHASISWA: PENDEKATAN AUTOETNOGRAFI - Dewi Muliasari (JURNAL ILMIAH EDUNOMIKA, 2026)
Strengthening students' scientific culture is a key focus of higher education in supporting the development of superior human resources. One strategic effort that can be undertaken is through innovative English language learning integrated with students' scientific contexts. This study aims to examine how innovative English language learning contributes to the growth of students' scientific culture in the Accounting Study Program through an autoethnographic approach. The study used a qualitative approach with an autoethnographic design, where the experiences of lecturers teaching English courses served as the primary data source, which were analyzed reflectively and critically. The study was conducted in the English course of the Accounting Study Program at ITB AAS Indonesia. Data were collected through lecturers' reflective journals, learning documentation, and student academic artifacts, then analyzed thematically by linking the findings to the theoretical framework of scientific culture, academic literacy, and English language learning based on scientific contexts. The results showed that innovative English language learning integrated with the accounting context was able to increase students' awareness of the function of English as an academic tool, encourage the development of basic academic literacy, and foster scientific attitudes such as courage to express opinions and active involvement in class discussions. Despite challenges related to differences in student language abilities and limited learning time, this study concludes that English language learning plays a strategic role in fostering a scientific culture in students in non-language study programs. The findings offer theoretical and practical implications for developing innovative English language learning in higher education.